Exploring the World Trade Organisation's Trade and Environment/Public Health Jurisprudence as a Model for Incorporating a Trade–Labour Linkage into the Organisation's Multilateral Trade Regime: Should African Countries Accept a Policy Shift?. Issue 1 (February 2017) - Warikandwa, Tapiwa V.; Osode, Patrick C.
Abstract : The incorporation of a trade-labour (standards) linkage into the multilateral trade regime of the World Trade Organisation (WTO) has been persistently opposed by developing countries, including those in Africa, on the grounds that it has the potential to weaken their competitive advantage. For that reason, low levels of compliance with core labour standards have been viewed as acceptable by African countries. However, with the impact of WTO agreements growing increasingly broader and deeper for the weaker and vulnerable economies of developing countries, the jurisprudence developed by the WTO Panels and Appellate Body regarding a trade-environment/public health linkage has the potential to address the concerns of developing countries regarding the potential negative effects of a trade-labour linkage. This article argues that the pertinent WTO Panel and Appellate Body decisions could advance the prospects of establishing a linkage of global trade participation to labour standards without any harm befalling developing countries.